Robust zeolitic tetrazole framework for electrocatalytic dopamine detection with high selectivity - Sarfudeen, Shafeeq; Sruthi, Vadakke Purakkal; Maibam, Ashakiran; Panda, Premchand; Jhariat, Pampa; Senthilkumar, Sellappan; BabaRao, Ravichandar; Panda, Tamas (Inorganic Chemistry, 2023)
A novel zeolitic tetrazolate framework (ZTF-8) has been synthesized by solvent-free heat-assisted (70 C-degrees) mechanochemical grinding of zinc acetate and 5-methyl tetrazole in the presence of NaOH powder. The structure of ZTF-8 adopts the zeolitic sodalite (SOD) topology with uncoordinated N-heteroatom sites and resembles the structure of the well-known zeolitic imidazole framework ZIF-8. ZTF-8 is exceptionally stable in 0.1 M aqueous acid and base solutions for 60 days at 25 C-degrees. The unique structure with uncoordinated N-heteroatom active sites and exceptional stability of ZTF-8 facilitated the electrocatalytic oxidation of dopamine to dopamine quinone at neutral pH. Without any postsynthetic modification, ZTF-8 is directly used for the facile electrochemical detection of dopamine over a wide range of concentrations (5-550 mu M) with a high sensitivity (2410.8 mu A mM-1 cm-2). It also demonstrated promising selectivity over other interferents of similar oxidation potential, such as ascorbic acid and uric acid. The DFT study revealed that the ZTF-8 framework has a higher binding energy (-145.07 kJ/mol) and stronger interaction with dopamine than its isostructural ZIF-8 structure (-130.42 kJ/mol).